GENETIC IMPROVEMENT OF WEANING WEIGHT, YEARLING WEIGHT, BODY WEIGHT GAIN AND BODY DIMENSION OF BALI CATTLE - Supriyantono, A.; Hakim, L.; Suyadi, S.; Ismudiono, I. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
The aim of the research was to evaluate the genetic improving of production traits selected of Balicattle. Four hundred and twenty eight data of weaning weight, yearling weight and body weight gainwere used to estimate genetic improvement for those traits. One hundred and seven data of bodydimension (body weight, chest circumference, body length and withers height) at 24 months old wereused to estimate genetic improving for those traits. The estimation of genetic and environmentalvariance and co-variance component, and heritability were found by animal model. The fix effect ofweaning weight, yearling weight and body weight gain was rainfall, age of measurement and year ofbirth, whereas the fix effect of body dimension depend on each trait. The result showed that heritabilityof weaning weight, yearling weight, body weight gain, body weight, chest circumference, body lengthand withers height was 0.090.15, 0.270.13, 0.470.15, 0.070.19, 0.500.19, 0.340.28, 0.600.21,respectively. Genetic improvement of all traits have had a different pattern in selection responses. Alltraits did not show genetic improvement due to selection for.